2021
DOI: 10.34172/hmj.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of heavy metals (Arsenic and Cadmium) in rice (Oryza sativa L.) brands imported to Iran: using Monte Carlo simulation

Abstract: Background: Rice contamination with heavy metals is one of the most common cases of environmental pollution. The purpose of this study was to investigate the concentration of heavy metals (arsenic and cadmium) in the most widely consumed rice brands imported to southern Iran and to assess the health risk of exposure to them for consumers. Methods: A total of 103 rice samples were selected from 10 brands imported from India during 2014-2018. Heavy metal concentrations were measured by dry ash method using atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, the mentioned study by Almutairi et al [ 33 ] from Saudi Arabia can be a suitable study for comparison. For example, Javdan et al [ 51 ] reported that the HQ values of Cd and As derived from the consumption of Indian rice in Hormozgan, Iran, were 1.7 × 10 −2 and 4.9 × 10 −1 , respectively. Another local study from Iranshahr, Iran, also reported an HI value of 6.67 among frequently consumed rice brands, and its biggest contributor was the As, with an HQ value of 5.23 (share of 78.41% in HI).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mentioned study by Almutairi et al [ 33 ] from Saudi Arabia can be a suitable study for comparison. For example, Javdan et al [ 51 ] reported that the HQ values of Cd and As derived from the consumption of Indian rice in Hormozgan, Iran, were 1.7 × 10 −2 and 4.9 × 10 −1 , respectively. Another local study from Iranshahr, Iran, also reported an HI value of 6.67 among frequently consumed rice brands, and its biggest contributor was the As, with an HQ value of 5.23 (share of 78.41% in HI).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study are comparable of previous studies, which have reported that the levels of arsenic, lead, and cadmium ranged from 0.21 to 0.98, 0.04 to 1.07, and 0.006 to 0.24 mg/kg, respectively, in brown rice near a mining area in Central China [19]. In a recent investigation of some imported rice varieties sold in the local markets of AlMadinah AlMunawarah, KSA, the results revealed that the country of origin affected the concentration of toxic metals (arsenic, cadmium, lead, and chromium) in rice grains, and the authors urged the regulatory authorities to monitor the heavy metal contents of rice imported in the Kingdom of Saudi Arabia [45,46]. The results clearly elucidated that both arsenic and lead contamination in brown rice can be a threat to human beings [44].…”
Section: Discussionmentioning
confidence: 99%